Modelling of economics regulations - Jakutis, Algirdas (Technological and Economic Development of Economy, 2004)
Economics may be presented in the form of corroborated rules. Economics may be defined as a science consisting of economic principles, laws, features, criteria, limitations, axioms, etc. Each listed entity may be divided into categories. Categories (category ‐ instruction) are theoretical concepts meaning the most important aspects of restoration of reality. Categories are forms giving theoretical meaning to practical experience. Categories give names to economic phenomena. Categories are presented and analysed in textbooks, reference books, and encyclopaedias. Categories are interconnected since the economic phenomena reflected by the categories are mutually connected. There are numerous relations among categories. These relations are like a network or a tree since one category is connected with several other categories, whereas the latter, in their own turn, are connected with the other categories. We may analyze the category “investment” as an example. The term “investments” is defined as the putting of capital into an enterprise. Capital is everything that has been created by the labour of people and it is being used for the manufacture of a final product. An enterprise is the production or commercial economic entity. Further, the following categories should be defined: labour, benefit, a product, production, commerce, and economy. Then the categories included in the above mentioned categories should be defined. A man models economic corroborated rules by means of a computer. The computer can find the main compositions to systematise the tremendous number thereof, quickly find necessary information, group corroborated rules, register and analyse them, and store information. However, the creation of a suitable program is quite a long and hard process. Corroborated rules which are regular and stable (are not variable) in real life may be simulated by a computer. A computer cannot apply the observation, verification, and genetic methods since it is only capable to analyse available information. Information changes very quickly and for this reason the results obtained are not accurate. The following distribution of work is possible: a man models separate (single) and couple compositions. The compositions consisting of three and a larger number of compounds are simulated by a computer. The identification of corroborated rules means that the types of corroborated rules taken out of the known economic text must be identified: laws, principles, features, and so on. It is quite easy to perform this work without using a computer provided that the volume of work is not large. However sometimes some doubts arise: to which type should a certain corroborated rule be attributed. Doubts are caused by the insufficiently accurate and simple definition of types of corroborated rules. While computerising the identification of economic corroborated rules it is important to accurately define the types of economic corroborated rules, then make algorithms and programs for the identification of each type of a corroborated rule. Identification enables to assess an economic text. The text the corroborated rules of which are presented in a certain order is acceptable for a reader. Consistent presentation facilitates the understanding of a text. Article in Lithuanian. Ekonomikos nuostatų modeliavimas First Published Online: 21 Oct 2010